2012
DOI: 10.1021/jo302086g
|View full text |Cite
|
Sign up to set email alerts
|

Selective Cross-Coupling of Organic Halides with Allylic Acetates

Abstract: A general protocol for the coupling of haloarenes with a variety of allylic acetates is presented. Strengths of the method are a tolerance for electrophilic (ketone, aldehyde) and acidic (sulfonamide, trifluoroacetamide) substrates and the ability to couple with a variety of substituted allylic acetates. Secondary alkyl bromides can also be allylated under slightly modified conditions, demonstrating the generality of the approach. Finally, the coupling of a reactive vinyl halide could be achieved by the use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
38
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(41 citation statements)
references
References 89 publications
2
38
0
1
Order By: Relevance
“…While most transformations based on activated alkyl electrophiles emphasize C(sp 3 )-C(sp 2 ) bond forming methods (see Sects. 2.2-2.5), the cross-coupling of allylic acetates (or carbonates) with unactivated alkyl halides represents the only example for the construction of hetero C(sp 3 )-C(sp 3 ) bonds utilizing activated alkyl electrophiles [36][37][38].…”
Section: Coupling With Activated Alkyl Electrophilesmentioning
confidence: 99%
See 3 more Smart Citations
“…While most transformations based on activated alkyl electrophiles emphasize C(sp 3 )-C(sp 2 ) bond forming methods (see Sects. 2.2-2.5), the cross-coupling of allylic acetates (or carbonates) with unactivated alkyl halides represents the only example for the construction of hetero C(sp 3 )-C(sp 3 ) bonds utilizing activated alkyl electrophiles [36][37][38].…”
Section: Coupling With Activated Alkyl Electrophilesmentioning
confidence: 99%
“…The Ni-catalyzed reductive coupling protocol enables allylation of a wide set of alkyl halides (Scheme 10) [36][37][38]. The reactions display excellent regioselectivities wherein addition of alkyl groups to the less hindered allylic positions is adopted.…”
Section: Coupling With Activated Alkyl Electrophilesmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously reported conditions have required stoichiometric additives (MgCl 2 , pyridine), long reaction times (24 h), or higher temperatures (40–80 °C), even with relatively high catalyst loadings (7–10 mol% nickel). [4b, 6] During our mechanistic studies, [5] we had found that the addition of TMS-Cl to the metallic reductant (Mn powder) accelerated the rate of cross-electrophile coupling reactions while maintaining selectivity at a given catalyst concentration. [7] We report here modified conditions that allow the selective coupling of a variety of vinyl bromides with primary and secondary alkyl halides.…”
mentioning
confidence: 99%